2018
DOI: 10.1177/1078345818782474
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Nutritional Quality of Commissary Foods Offered in American Women’s Prisons

Abstract: Weight gain and obesity among female prisoners is of public health concern. This study analyzed the nutritional quality of commissary food and recipes cooked within eight women's prisons in the United States. Food items from commissary lists were categorized into the MyPlate food groups. Nutrition Data System for Research was used to analyze the nutritional content of recipes ( N = 175). Mean nutrient content, percent Daily Values, and food group servings were calculated. Recipes were generally high in sodium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Other research utilized “percent daily value”, which equates to the DRI, as their comparative value for sodium. If compared to the DASH recommendations, recipes prepared from commissary foods would equate to 134% of DASH recommendations (Rosenboom et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research utilized “percent daily value”, which equates to the DRI, as their comparative value for sodium. If compared to the DASH recommendations, recipes prepared from commissary foods would equate to 134% of DASH recommendations (Rosenboom et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An additional study by Firth et al in 2015 evaluated commissary provisions independently from the menu and found the provisions were in excess of recommended daily calories (≥50%) and did not meet United States Department of Agricultural (USDA) Smart Snack Guidelines (Firth et al , 2015). Finally, a study by Rosenboom et al (2018) concluded that commissary items provided excess calories, sodium and fat. However, their analysis was based on a recipe book of typical meals prepared using commissary items rather than evaluating the individual items themselves (Rosenboom et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While commissary foods can contribute to calorie and macronutrient intake, limited research has explored the relationship between commissary foods and dietary impact. Researchers previously determined an average of 1,000 kcal per day was purchased daily at a commissary in a women’s jail in Oregon [ 16 ] and another group found that commissary meals provided excess calories, sodium, and fat [ 17 ]. However, a recipe book was used to analyze meals commonly prepared using commissary items rather than evaluate the individual items [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers previously determined an average of 1,000 kcal per day was purchased daily at a commissary in a women's jail in Oregon [16] and another group found that commissary meals provided excess calories, sodium, and fat [17]. However, a recipe book was used to analyze meals commonly prepared using commissary items rather than evaluate the individual items [17]. No known study has assessed the Conclusions: Exceeding caloric and saturated fat recommendations may contribute to weight gain, regardless of high diet quality.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, Wangmo et al (2018) mentioned that older prisoners reported the need to improve the food provided in prison due to it not being tailored to their needs and its poor quality. Similarly, in a study on the quality of commissary foods offered to women prisoners in the USA, Rosenboom et al (2018) found that recipes were generally high in sodium, saturated fat, added sugars and calories but low in vitamin D. Moloko et al (2018) observed that the food situation is much worse in Malawi's prisons because prisoners generally eat one meal per day. According to Gould et al (2013), prisoners incarcerated in developing countries have been shown to be vulnerable to dietary deficiencies.…”
Section: Introductionmentioning
confidence: 99%